2021
DOI: 10.1007/s00228-021-03223-9
|View full text |Cite
|
Sign up to set email alerts
|

Sports nutrition supplements and adverse events – a meta-epidemiological study of case reports specifically addressing causality assessment

Abstract: Purpose This meta-epidemiological study aimed to systematically review case reports regarding sports nutrition supplements and adverse events (AEs), specifically addressing the issue of causality assessments. Methods Through a systematic literature search we identified all published case reports of AEs associated with sports nutrition supplements between 1 January 2008 and 1 March 2019. Data regarding AEs, suspected supplements, relevant causality assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The tool, will help to guide discussion between sports health professionals about the need of specific supplements. Taking in account that there are many challenges, like problems with time management [34] and/or limited professional support [35], sports health professionals need to reserve time as part of their team work to agree on the topic of meaningful and safe supplement usage to ensure athletes are served with the highest quality of advice [36].…”
Section: Discussionmentioning
confidence: 99%
“…The tool, will help to guide discussion between sports health professionals about the need of specific supplements. Taking in account that there are many challenges, like problems with time management [34] and/or limited professional support [35], sports health professionals need to reserve time as part of their team work to agree on the topic of meaningful and safe supplement usage to ensure athletes are served with the highest quality of advice [36].…”
Section: Discussionmentioning
confidence: 99%
“…8 Zeijon et al revealed that "Protein,DMAA, Cafeine, Creatine, Methasteron, Testosterone, Anabolic steroid, Synephrine, Methylstenbolone, Nandrolone, Citrus aurantium" were the most reportedsupplements for adverse effects. 3 In Turkey, especially in the Trakya region, "Glucosamine Chondritin, Biotin (vitamin B7), Coenzyme Q-10, Panax Ginseng, St.John's Wort, Vitamin B12, Vitamin C, Vitamin D3, Multivitamins, Iron, Calcium, Magnesium, Zinc Folic Acid (vitamin B9), Fish Oil (Omega 3, 6, 9 Fatty acids)" wasreported as most frequently used supplements. 9 Campbell et al reported that thereason to use supplements were "Key themes that influenced supplement usewere weight loss, body image, nutrition, training, education, challenges, need,and time."…”
Section: Discussion Discussionmentioning
confidence: 99%
“…However, it is important to not undervalue the risk of fatal side effects in young adults, particularly cardiovascular side effects. 3,5 According to a research which was published in 2021; especially 1,3-dimethylamylamine is the most detected supplement in doping samples. So we can say that 1,3-dimethylamylamine has a very common use as doping in the atletics.…”
Section: Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large-scale use of these supplements, their adverse health effects are poorly investigated. Over the years, several cases of serious adverse health effects, like palpitations, myocardial infarction, cardiac arrest and brain haemorrhages, have been linked to the use of pre-workout and fat burner supplements [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Most of these adverse health effects are specifically associated with the cardiovascular system [ 10 ].…”
Section: Introductionmentioning
confidence: 99%